A diverse set of microRNAs and microRNA-like small RNAs in developing rice grains - Zhu, Qian-Hao; Spriggs, Andrew; Matthew, Louisa; Fan, Longjiang; Kennedy, Gavin; Gubler, Frank; Helliwell, Chris (Genome Research, 2008)
Endogenous small RNAs, including microRNAs (miRNAs) and short-interfering RNAs (siRNAs), function as post-transcriptional or transcriptional regulators in plants. miRNA function is essential for normal plant development and therefore is likely to be important in the growth of the rice grain. To investigate the roles of miRNAs in rice grain development, we carried out deep sequencing of the small RNA populations of rice grains at two developmental stages. In a data set of ∼5.5 million sequences, we found representatives of all 20 conserved plant miRNA families. We used an approach based on the presence of miRNA and miRNA* sequences to identify 39 novel, nonconserved rice miRNA families expressed in grains. Cleavage of predicted target mRNAs was confirmed for a number of the new miRNAs. We identified a putative mirtron, indicating that plants may also use spliced introns as a source of miRNAs. We also identified a miRNA-like long hairpin that generates phased 21 nt small RNAs, strongly expressed in developing grains, and show that these small RNAs act in trans to cleave target mRNAs. Comparison of the population of miRNAs and miRNA-like siRNAs in grains to those in other parts of the rice plant reveals that many are expressed in an organ-specific manner.